Estimating potential savings in cancer deaths by eliminating regional and social class variation in cancer survival in the Nordic countries. Issue 3 (June 1997) - Dickman, P W; Gibberd, R W; Hakulinen, T
Abstract : STUDY OBJECTIVES: To examine equity in the health care system with regard to cancer patient care by estimating the level of systematic regional variation in cancer survival in the Nordic countries. Specifically, those cancer sites which exhibit high levels of systematic regional variation in survival and hence inequity were identified. Estimating the reduction in cancer deaths which could be achieved by eliminating this variation so that everyone receives effective care will provide a readily interpretable measure of the amount of systematic regional variation. A comprehensive analysis of regional variation in survival has not previously been conducted so appropriate statistical methodology must be developed. SETTING AND PARTICIPANTS: All those aged 0-90 years who had been diagnosed with at least one of 12 common malignant neoplasms between 1977 and 1992 in Denmark, Finland, Norway, and Sweden. DESIGN: A separate analysis was conducted for each country. Regression models for the relative survival ratio were used to estimate the relative risk of excess mortality attributable to cancer in each region after correcting for age and sex. An estimate of the amount of systematic regional variation in survival was obtained by subtracting the estimated expected random variation from the observed regional variation. An estimate was then made of the potential reduction in the number of cancer deaths for 2008-12 if regional variation in survival were eliminated so that everyone received the same level of effective care. MAIN RESULTS: Between 2008 and 2012, an estimated 2.5% of deaths from cancers in the 12 sites studied could be prevented by eliminating regional variation in survival. The percentage of potentially avoidable deaths did not depend on country or sex but it did depend on cancer site. There was no relationship between the level of regional variation in a given country and the level of survival. The cancer sites for which the greatest percentage savings could be achieved were melanoma (11%) and cervix uteri (6%). The sites for which the highest number of deaths could be prevented were prostate, colon, melanoma, and breast. CONCLUSIONS: This methodology showed a small amount of systematic regional variation in cancer survival in the Nordic countries. The cancer sites with high levels of regional variation identified are potential targets for cancer control programmes.